Perbandingan Pengamatan Benchmark Menggunakan Alat Spectra SP80 dan Comnav T300 dengan Software Trimble Business Center - Yunadi Arham; Dawamul Arifin; Feri Fadlin; Andi Baso Sofyan A. P. (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2025)
The GNSS survey method is currently widely used for various purposes, both scientific and practical, due to its advantages in terms of accuracy, speed, simplicity, and lower cost. Today, a wide range of GNSS survey instruments are available for benchmark point observations. Therefore, it is necessary to obtain information regarding the accuracy that these different instruments can provide. This study compares the results of benchmark point observations using the same method, namely the static method, but with two different instruments: Spectra SP80 and Comnav T300. The aim of this research is to determine the accuracy level of benchmark observations using the Spectra SP80 and Comnav T300, processed with the Trimble Business Center application. The comparative analysis shows that the Spectra SP80, when processed using Trimble Business Center, produces a smaller average difference in X and Y coordinates compared to the Comnav T300. However, in the Z coordinate, the Comnav T300 shows a smaller average difference than the Spectra SP80. Data analysis from the processing summary images provides information on the precision levels of both instruments. At benchmark point BM 2, the Comnav T300 demonstrated superior horizontal and vertical precision compared to the Spectra SP80. Conversely, at benchmark point BM 5, the Spectra SP80 showed better horizontal and vertical precision than the Comnav T300.